2000
DOI: 10.1177/03635465000280011701
|View full text |Cite
|
Sign up to set email alerts
|

The Stabilizing Sling for the Long Head of the Biceps Tendon in the Rotator Cuff Interval

Abstract: A histoanatomic study of the rotator cuff interval was done in 13 cadaveric specimens to investigate the relation of its ligamentous structures to the long head of the biceps tendon, with a special focus on revealing a stabilizing function. After macroscopic evaluation, the lateral half of the rotator cuff interval capsule was cut into three sections: medial, middle, and lateral. These sections were embedded in methacrylate, and then serial sections were made and stained for polarized light microscopy. The sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(73 citation statements)
references
References 22 publications
2
67
0
4
Order By: Relevance
“…The exact location of labral attachment varies, but is usually in the posterior portion of the superior labrum. 18,60 The intra-articular portion of the LHB tendon is partially stabilized by the biceps reflection pulley, which consists of the superior glenohumeral ligament (SGHL), the coracohumeral ligament, and deep fibers of the subscapularis and supraspinatus tendons 64 (Fig. 1).…”
Section: Anatomymentioning
confidence: 99%
“…The exact location of labral attachment varies, but is usually in the posterior portion of the superior labrum. 18,60 The intra-articular portion of the LHB tendon is partially stabilized by the biceps reflection pulley, which consists of the superior glenohumeral ligament (SGHL), the coracohumeral ligament, and deep fibers of the subscapularis and supraspinatus tendons 64 (Fig. 1).…”
Section: Anatomymentioning
confidence: 99%
“…2,21,98 We believe that the coracoglenohumeral ligament inserts onto both margins of the groove together with the anterior limb of the rotator cable. The tendons of the supraspinatus and of the subscapularis rarely cover the groove.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the superior and inferior complexes may be linked to each other medially, through the glenoid labrum, as well as laterally, through the fasciculus obliquus. Werner et al 98 already reported that the fasciculus obliquus makes an important contribution to the biceps pulley together with the superior glenohumeral ligament. The potential implications of the superior complex and the linkage between both complexes for glenohumeral stability require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotatoreninter vallschlinge ("reflection pulley") verläuft. Diese Schlinge wird zum einen aus dem coracohumeralen Band (CHL), das von der Basis und der lateralen Facette des Coracoids zum Vorderrand des M. su praspinatus und mit zwei Schenkeln am Tuberculum minus und majus inseriert, und zum anderen vom superioren gleno humeralen Band (SGHL) gebildet, das aus dem kapsulären Ansatzbereich des Tuber culum supraglenoidale entspringt und als kapsuläres Verstärkungsband Uförmig unterhalb der langen Bizepssehne zum Oberrand des Tuberculum minus zieht [32]. Das SGHL und das CHL bilden so eine Schlinge aus, die wie ein Ringband die lange Bizepssehne sichert, noch bevor diese in den Sulcus bicipitalis eintaucht.…”
Section: Anatomie Und Arthroskopische Visualisierungunclassified